Análisis a los estados financieros de la "cooperativa de ahorro y crédito Textil 14 de Marzo" cantón Rumiñahui, provincia Pichincha periodo 2014-2015 - Tobar Flores, Alicia Aracely (2017)
The present thesis was developed with the objective of analyzing the behavior of the items that make up the Financial Statements of this institution during these two periods; Through the application of financial indicators and the vertical and horizontal analysis. Also it is emphasized that the development of the work is structured based on the regulations of the National University of Loja to obtain the Degree of Engineer in Accounting and Auditing, CPA. It is important that any company perform the analysis of financial statements and use as a tool indicator; these serve as a strategy to organize, plan and project to the company in the medium and long term in a safe manner. For this reason, the analysis horizontal and vertical to the balance sheets of the cooperative was known the degree of representativeness of each item compared to your group, and the variation of active, passive, heritage, expenses and revenues. It complied with the implementation of the PEARLS system and Dupont to know the indicators of solvency, liquidity, management, margin of profitability. Finally, it is noted that the organization operates in normal conditions from the point of view of the financial and economic; it is necessary to reduce nonperforming loans and operating expenses with the aim of improving the profitability of the savings and credit cooperative.